The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1678-4162-10792
|View full text |Cite
|
Sign up to set email alerts
|

Thyme essential oil for sheep: effect on rumen fermentation, nutrient digestibility, nitrogen metabolism, and growth

Abstract: Óleo essencial de tomilho para ovinos: efeito na fermentação ruminal, na digestibilidade dos nutrientes, no metabolismo de nitrogênio e no crescimento]A. ABSTRACTTwo experiments were conducted to evaluate the effect of thyme (Thymus vulgaris) essential oil (EO) doses on rumen fermentation, nutrient digestibility, and nitrogen metabolism, as well as performance and coccidia oocyst discharge. In experiment I, 20 rumen-cannulated wethers received the experimental diets containing 80% dry matter (DM) of haylage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(25 reference statements)
0
10
1
1
Order By: Relevance
“…Of these, 12 studies were eligible for the current meta-analysis. The essential oil sources included oregano 11 , 22 – 24 , thyme 25 , 26 , chavil 27 , juniper 7 , 28 , and mixed product 9 , 29 . Unfortunately, one study did not define the source of essential oil 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 12 studies were eligible for the current meta-analysis. The essential oil sources included oregano 11 , 22 – 24 , thyme 25 , 26 , chavil 27 , juniper 7 , 28 , and mixed product 9 , 29 . Unfortunately, one study did not define the source of essential oil 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Primitive breeds kept on organic farms get sick less frequently as compared to conventional farms or even more large-scale breeding [ 32 ]. Their treatment is based primarily on the use of natural substances of plant origin e.g., the essential oils (based on thyme, cinnamon, lemongrass, oregano, and rosemary) [ 66 , 67 ] and herbs (garlic, onion, dill, parsley, mint) which constitute an alternative to antibiotics and other conventional antimicrobial drugs [ 68 ]. All the animals included in our study were healthy and had never been treated with any antimicrobials or antiseptics.…”
Section: Discussionmentioning
confidence: 99%
“…In general, essential oils have a positive influence when administrated with dairy sheep rations. Adding 1.25 g/kg DM of thyme essential oil improved both ruminal fermentation and nitrogen metabolism [ 48 ]. Another study investigating the effects of oregano essential oils on sheep showed an increase in the population of three primary cellulosic bacteria and ruminal fungi, affecting the rumen fermentation process [ 49 ].…”
Section: Discussionmentioning
confidence: 99%